The Nexus of Rainwater Harvesting: Bridging Engineering Solutions with Socioeconomic Strategies for Safe Adoption - Acharya, Prabesh; Khanal, Preju; Thapa, Bijay; Karki, Bhesh Kumar (Sustainability & Circularity NOW, 2025)
Rainwater harvesting (RWH) is increasingly being recognized as a sustainable alternative water source, yet questions about its safety and wider acceptance remain unresolved. A qualitative narrative synthesis was employed, drawing on evidence from peer-reviewed literature, identified from major databases and chosen for their methodological rigor, relevance, and geographical spread, focusing on the interplay between engineering, environmental, and socio-economic factors influencing RWH system performance. Data extraction included roofing material type, contaminant profiles, seasonal influences, storage design, first-flush performance, and adoption drivers.Evidence reveals the decisive role of system configuration, and roofing materials as ceramic and stone-coated tiles, along with well-maintained galvanized steel, tend to produce water with comparatively lower microbial and heavy metal contamination, while asphalt, green roofs, and some metallic surfaces often pose potential human health risks. Local environmental conditions such as seasonal variation, atmospheric deposition, and neighborhood pollution add further complexity to quality outcomes. Although first-flush systems reduce initial loads of contaminants, treatment remains necessary for potable use, and the type of storage tank continues to influence both microbial persistence and chemical leaching.Socio-economic factors strongly influence adoption and maintenance, underscoring that technical optimization alone is insufficient. These interactions are conceptualized within the proposed Integrated Socio-Technical-Environmental (ISTE) Framework. Together, these findings point to the importance of material-specific guidelines, robust first-flush systems, affordable treatment technologies, and supportive policy frameworks to ensure harvested rainwater safety. Further research should integrate real-time monitoring, address emerging pollutants, and link engineering solutions with socio-economic strategies for broader adoption.
Keywords: Rainwater harvesting; Water quality; Storage systems; Roofing materials; Socio-economic factors; Environmental influences; Heavy metals; ISTE